2018
DOI: 10.3390/w10101490
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Curtailment: Evaluating Water Management Practices in the Context of Changing Runoff Regimes in a Snowmelt-Dominated Basin

Abstract: Hydrologic scientists and water resource managers often focus on different facets of flow regimes in changing climates. The objective of this work is to examine potential hydrological changes in the Upper Boise River Basin, Idaho, USA in the context of biophysical variables and their impacts a key variable governing administration of water resources in the region in an integrated way. This snowmelt-dominated, mountainous watershed supplies water to a semi-arid, agriculturally intensive, but rapidly urbanizing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…As previously stated, the upstream surface water hydrology boundary condition in the Lower Boise River Basin corresponds to the hydrologic output of a system of large reservoirs within the UBRB, a snow-dominated, mountain, largely forest-covered watershed. Although climate change, particularly in the form of shifts in the precipitation phase from snow to rain, is expected to significantly alter hydrologic regimes in the UBRB [2], we do not consider these potential changes in order to reduce the complexity of our analysis. As such, the upstream inflow boundary to our simulation domain (the discharge from the Lucky Peak Reservoir) is set to be the same as a normal year, taking 2012 as an example.…”
Section: Coupled Socio-hydrology Systems Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously stated, the upstream surface water hydrology boundary condition in the Lower Boise River Basin corresponds to the hydrologic output of a system of large reservoirs within the UBRB, a snow-dominated, mountain, largely forest-covered watershed. Although climate change, particularly in the form of shifts in the precipitation phase from snow to rain, is expected to significantly alter hydrologic regimes in the UBRB [2], we do not consider these potential changes in order to reduce the complexity of our analysis. As such, the upstream inflow boundary to our simulation domain (the discharge from the Lucky Peak Reservoir) is set to be the same as a normal year, taking 2012 as an example.…”
Section: Coupled Socio-hydrology Systems Modelmentioning
confidence: 99%
“…We do not consider population and land use change, which are both important changing factors for future water use projections. We also assume that the recharge into the watershed boundary keeps constant between years; however, research has shown that recharge from Upper Boise Watershed to the study area will change under future climate change scenarios [2]. In addition, we also assume that water rights will remain the same in the future.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Snowmelt is one of the processes intervening in the hydrological cycle and interacting with many other processes. This article focuses on the phenomenon of melt-induced flooding and the changes it causes in the runoff regime, but this issue and its consequences have already been widely studied using a multitude of approaches [1,2].…”
Section: Introductionmentioning
confidence: 99%